Pengaruh Gaya Kepemimpinan Transformasional Kepala Sekolah dan Motivasi Kerja Terhadap Kinerja Guru - Rina Hasna; Agustina, Granit (Mansion: Management and Business on Kebangsaan, 2025)
Introduction: Teacher performance is pivotal to learning quality in Indonesian schools, and two levers— principals’ transformational leadership and teachers’ work motivation— are frequently cited but unevenly enacted across Islamic education foundations. Background Problems: Many schools report inconsistent teacher performance; the research question is: To what extent do the principal’s transformational leadership style and teachers’ work motivation affect teacher performance, both individually and jointly? Novelty: Prior work rarely quantifies the simultaneous effects of these constructs within Islamic educational foundations; this study adds context-specific evidence by examining a single foundation and linking leadership behaviors with motivation in one model. Research Methods: A quantitative, associative design was used at the Darul Muttaqin Islamic Education Foundation (n = 44 teachers). Data were collected via validated questionnaires and analyzed using multiple linear regression (SPSS 25) with t-tests (partial) and F-tests (simultaneous). Finding/Results: Both transformational leadership and work motivation significantly improve teacher performance; the model is significant (F = 18.186 > 3.23, p < 0.05), shows a moderate multiple correlation (R = 0.567), and explains substantial variance (R² = 0.831). Conclusion: Enhancing principals’ transformational practices together with systematic motivation initiatives (recognition, development opportunities, supportive facilities) can meaningfully raise teacher performance in Islamic secondary schools and should be prioritized in leadership and HR policies.